Pharmacogenetics of ovarian response. (April 2014) - Lledo, Belen; Ortiz, Jose A; Llacer, Joaquin; Bernabeu, Rafael
Effective controlled ovarian stimulation (COS) is crucial for IVF outcome. Ovarian response to follicle-stimulating hormone, however, varies widely among women undergoing ovarian stimulation. Advance identification of patients who will elicit a poor or high response to standard treatment would be of great clinical benefit for such patients. Application of pharmacogenetics to ovarian response may predict stimulation success but also help in the adjustment and design of doses prior to treatment. Different studies have examined the impact of variations in follicle-stimulating hormone receptor, biochemical pathways involved in estrogen production and action, folliculogenesis and other aspects. Recently, gene-association studies have tried to identify a number of genetic variations affecting interindividual variability in COS.